Introducing Improved Iterated Extended Kalman Filter (IIEKF) to Estimate the Rotor Rotational Speed, Rotor and Stator Resistances of Induction Motors - Bijan Moaveni; Zahra Masoumi; Pegah Rahmani (IEEE Access, 2023)
This paper introduces the Improved Iterated Extended Kalman Filter (IIEKF) for estimating the rotational speed, rotor resistance, and stator resistance of three-phase induction motors (IMs). Two state-space models for estimating the variables are presented. An optimal estimation of rotational speed is obtained by introducing a data fusion approach. The effectiveness of the IIEKF in comparison with the Extended Kalman Filter (EKF), using experimental data and in a wide range of operating conditions, is shown.